Multiplexed reverse transcription real-time polymerase chain reaction for simultaneous detection of Mayaro, Oropouche, and Oropouche-like viruses - Felipe Gomes Naveca; Valdinete Alves do Nascimento; Victor Costa de Souza; Bruno Tardelli Diniz Nunes; Daniela Sueli Guerreiro Rodrigues; Pedro Fernando da Costa Vasconcelos (Memorias do Instituto Oswaldo Cruz)
ABSTRACT We describe a sensitive method for simultaneous detection of Oropouche and Oropouche-like viruses carrying the Oropouche S segment, as well as the Mayaro virus, using a multiplexed one-step reverse transcription real-time polymerase chain reaction (RT-qPCR). A chimeric plasmid containing both Mayaro and Oropouche targets was designed and evaluated for the in vitro production of transcribed RNA, which could be easily used as a non-infectious external control. To track false-negative results due to PCR inhibition or equipment malfunction, the MS2 bacteriophage was also included in the multiplex assay as an internal positive control. The specificity of the multiplex assay was evaluated by Primer-Blast analysis against the entire GenBank database, and further against a panel of 17 RNA arboviruses. The results indicated an accurate and highly sensitive assay with amplification efficiency greater than 98% for both targets, and a limit of detection between two and 20 copies per reaction. We believe that the assay described here will provide a tool for Mayaro and Oropouche virus detection, especially in areas where differential diagnosis of Dengue, Zika and Chikungunya viruses should be performed.